Development and reproduction of Ceraeochrysa cubana (Neuroptera: Chrysopidae) fed with Aleurocanthus woglumi (Hemiptera: Aleyrodidae) - Robério de Oliveira (Semina: Ciências Agrárias, 2016)
This study evaluated the development and reproduction of Ceraeochrysa cubana when fed the citrus blackfly Aleurocanthus woglumi. The study was carried out at the Laboratory of Entomology, Department of Plant and Environmental Sciences, Federal University of Paraíba of Areia/PB. It used a completely randomized design. The study was conducted in climate chambers, regulated to 26 ± 2°C and a relative humidity of 70 ± 10% with a 12 h photoperiod. The treatments were as follows: eggs, nymphs of only the 1st, 2nd, 3rd, or 4th instars, and nymphs of multiple instars (1st, 2nd, 3rd, and 4th instars) of A. woglumi, with eggs of Sitotroga cerealella as a control. The 1st instar of C. cubana lasted 5.8 to 10.7 days, the 2nd instar lasted 6.0 to 13.3 days, and the 3rd instar lasted 8.2 to 18.5 days. The larvae of C. cubana did not survive when the food provided was only the eggs of A. woglumi, since the predator could not eat them. C. cubana, when provided nymphs of multiple instars (1st, 2nd, 3rd, and 4th instars) of the citrus blackfly, had a shorter pre-pupal period and lower longevity than when consuming the eggs of S. cerealella, but the sex ratio and oviposition period were not affected. However, changes occurred in the pre-oviposition period, the total number of eggs, and the number of viable eggs.